HUBUNGAN OBESITAS DENGAN KEJADIAN DIABETES MELLITUS TIPE 2 DI PUSKESMAS WATES KABUPATEN KULON PROGO TAHUN 2013 - , Dian Rosadi ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Diabetes mellitus is one type of non-communicable diseases with increasing prevalence. In the D. I. Yogyakarta province and Kulon Progo District diabetes cases continue to increase each year as well as in Wates health centers, DM ranks fourth highest in number of cases compared to other non-communicable diseases. Obesity is strongly associated with diabetes mellitus, especially type 2 diabetes in which the prevalence of Type 2 diabetes in line with the increasing prevalence of obesity, about 80% of people with Type 2 diabetes are obese. This study was conducted to examine the relationship between obesity and the occurence of type 2 diabetes mellitus in Wates health center, Kulon Progo District. Method: The type of this study is observational analytic study with cross sectional design. The population of this study were all residents aged 18-60 years sampled using consecutive sampling. Statistical analysis was performed using chi square test and logistic regression using STATA 12.1 software. Results: The subjects of this study were 376 people. Based on logistic regression analysis, the variables that have statistically and practically significance are obesity variables based on body mass index (BMI) (OR 2.51 and CI: 1.49 to 4.23), and obesity variables based waist circumference (WC) (OR 1.79 and CI: 1, 06 to 3.02). Meanwhile, there was no significant relationship between obesity variables based waist to hip ratio (WHR) and occurence of type 2 diabetes (OR 1.38, and CI: 0.81 to 2.33). Conclusion: There is a significant relationship between obesity based on the BMI and WC and type 2 DM occurence while WHR has no significant relationship with the occurence of type 2 DM in Wates health center Kulon Progo District. It is expected from the community to perform control over changes either in body shape, weight or waist circumference, with routine measurement.